6 - Roles, Stress and Coping Mechanisms among Middle-level Academic Leaders in Multi-campus Universities in Africa - Atibuni, Dennis Zami (Journal of Higher Education in Africa, 2022)
Using a critical review of literature and existing data, this article explicates the roles of middle-level academics and the stress factors that hinder their efficient and effective delivery of academic and managerial roles in multi- campus universities in Africa. The article presents both plausible and actual coping mechanisms for middle-level academic leaders. It is noted that most middle- level academic leaders ascend to positions of responsibility without any formal training for these positions, which strengthens the call for the university to offer continuous training programmes for these leaders. The article argues that an effective identification and resolution of stress in the multi-campus system is key to winning and maintaining the morale and loyalty of staff at the university. This therefore calls for the adoption of appropriate theoretical paradigms of leadership in multi-campus universities for effective middle- level academic leadership. Recommendations are provided in the form of roles of the university in how to best enhance the productivity of this cadre of university leaders in achieving the functions of teaching, research, and community service.